2014
DOI: 10.1186/1471-2458-14-922
|View full text |Cite
|
Sign up to set email alerts
|

Co-interviewing across gender and culture: expanding qualitative research methods in Melanesia

Abstract: BackgroundThe social and cultural positions of both researchers and research participants influence qualitative methods and study findings. In Papua New Guinea (PNG), as in other contexts, gender is a key organising characteristic and needs to be central to the design and conduct of research. The colonial history between researcher and participant is also critical to understanding potential power differences. This is particularly relevant to public health research, much of which has emerged from a positivist p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 21 publications
3
12
0
Order By: Relevance
“…One assumed advantage was an elimination of imbalanced gendered power dynamics between the researcher and the participants. Collective experience with research on sexuality and GBV suggests that gender-matching between interviewer and participants increases honest disclosure (Byrne, 2004; Redman-MacLaren et al, 2014). In terms of disadvantages, participants may not have elaborated on information which they assumed that the researcher already knew.…”
Section: Methodsmentioning
confidence: 99%
“…One assumed advantage was an elimination of imbalanced gendered power dynamics between the researcher and the participants. Collective experience with research on sexuality and GBV suggests that gender-matching between interviewer and participants increases honest disclosure (Byrne, 2004; Redman-MacLaren et al, 2014). In terms of disadvantages, participants may not have elaborated on information which they assumed that the researcher already knew.…”
Section: Methodsmentioning
confidence: 99%
“…Beyond gender, co-interviewing might magnify the voices of participants who are marginalised by virtue of other aspects of identity, such as sexuality, race or language. Burnard (2004) and Redman-Maclaren et al (2014) both assert that co-interviewing can provide benefits for culturally focused research, where including a cultural 'insider' and 'outsider' researcher can facilitate interpretation, understanding, and bridge cultural divides. Indeed, in their research with Punjabi women with rheumatoid arthritis, Sanderson et al (2013) observed some benefits of including a co-researcher in the interviews, who provided language interpretation, where participants did not have sufficient proficiency in English.…”
Section: Bridging Dividesmentioning
confidence: 99%
“…However, few recent studies have explicitly examined the experience of having two researchers actively conduct the same interview. In fact, with the rare exception of work conducted by Redman-Mclaren et al (2014), no recent literature has specifically interrogated the process of co-interviewing in qualitative research. Clearly, for two researchers to conduct an interview with one participant, there are concerns surrounding an inherent power imbalance, by mere virtue of outnumbering.…”
Section: Introductionmentioning
confidence: 99%
“…However, FJ’s outsider position compelled him to scrutinize certain issues more closely, instead of accepting all the interpreter’s feedback, as suggested by Suwankhong and Liamputtong (2015). The experience in this study demonstrated the value of co-interviewing as a mechanism to blunt the influence of the insider and outsider in research with cultural and gender divides (Redman–MacLaren et al, 2014).…”
Section: Discussionmentioning
confidence: 82%